2000
DOI: 10.1042/bj3510811
|View full text |Cite
|
Sign up to set email alerts
|

Shared control of hepatic glycogen synthesis by glycogen synthase and glucokinase

Abstract: We have used recombinant adenoviruses (AdCMV-RLGS and AdCMV-GK) to overexpress the liver isoforms of glycogen synthase (GS) and glucokinase (GK) in primary cultured rat hepatocytes. Glucose activated overexpressed GS in a dose-dependent manner and caused the accumulation of larger amounts of glycogen in the AdCMV-RLGS-treated hepatocytes. The concentration of intermediate metabolites of the glycogenic pathway, such as glucose 6-phosphate (Glc-6-P) and UDP-glucose, were not significantly altered. GK overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…3C) and glycogen content (31.7 Ϯ 3.4 and 67.2 Ϯ 6.9 g/10 6 cells, respectively) (Fig. 3A) of AdCMV-GK-infected hepatocytes treated with 5 or 25 mM glucose also rose significantly and in a glucose-concentration dependent manner, as described previously (1).…”
Section: Resultssupporting
confidence: 86%
“…3C) and glycogen content (31.7 Ϯ 3.4 and 67.2 Ϯ 6.9 g/10 6 cells, respectively) (Fig. 3A) of AdCMV-GK-infected hepatocytes treated with 5 or 25 mM glucose also rose significantly and in a glucose-concentration dependent manner, as described previously (1).…”
Section: Resultssupporting
confidence: 86%
“…Only when blood sugar concentration increases above a threshold level does GK translocate to the cytosol and start to produce Glc-6-P, thus giving the signal that triggers the synthesis of hepatic glycogen. In this case, the control of glycogen synthesis is not exerted by glucose transport but rather by GK and GS (8). It appears that the inability of the Glc-6-P produced by HK I to stimulate the activation of LGS is one way for the hepatocyte to ensure that hepatic glycogen synthesis is only engaged when needed, that is when blood glucose levels are high.…”
Section: Discussionmentioning
confidence: 95%
“…The nitrocellulose blot was incubated overnight at 4°C in blocking buffer (1% bovine serum albumin, 0.05% Tween 20 in phosphate-buffered saline). The blot was then incubated for 1 h at room temperature with a rabbit antibody against rat LGS (8), human MGS (14), or rat GK (21) or a mouse antibody against rat HK I (Chemicon), washed, and then incubated for 1 h with a secondary anti-rabbit (Amersham Biosciences) or anti-mouse (Dako, Glostrup, Denmark) antibody conjugated to horseradish peroxidase. Immunoreactive bands were visualized using an ECL kit (Amersham Biosciences) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose transport and phosphorylation are the first steps in glucose utilization in the liver, where GK contributes to glucose disposal. Several studies in vitro have shown that GK activation is needed for glycolysis and glycogen synthesis [1,2,3,4]. Similarly, in transgenic liquid N 2 .…”
mentioning
confidence: 96%